OPTIMASI MEDIA SUBSTRAT UNTUK KEBERHASILAN BUDIDAYA SELADA (Lactuca sativa L.) PADA SISTEM HIDROPONIK - Utami, Angki Intan; Fahmi, Kurniawan (Institute of Computer Science (IOCS), 2025)
Dry land is an obstacle to meeting the increasing demand for lettuce (Lactuca sativa L.) in Gunungkidul, so hydroponic system has been applied, where its success is largely determined by the composition of the growing media used. This study aimed to determine the most suitable substrate medium to support the success of hydroponic lettuce cultivation. The experiment was conducted using three treatments: M1 (rice husk charcoal + manure, 1:1), M2 (cocopeat + manure, 1:1), and M3 (sand + manure, 1:1), each replicated 15 times with a total of 45 plants. The observed variables included plant survival percentage (%) and fresh weight (gram) at harvest. Data were analyzed using analysis of variance (ANOVA) followed by Tukey’s HSD test at the 5% significance level. The results showed that the substrate media had a significant effect on both observed variables. Treatment M2 (cocopeat + manure) produced the highest plant survival percentage and fresh weight, which was significantly different from M3 (sand + manure), while M1 (rice husk charcoal + manure) showed no significant difference from either treatment. Therefore, the combination of cocopeat + manure was identified as the most optimal substrate medium for hydroponic lettuce cultivation on dry land in Gunungkidul.